PW 0673 The changing opioid overdose epidemic in the united states – CDC response. (November 2018) - Baldwin, Grant; Noonan, Rita; Haegerich, Tamara; Dowell, Debbie; Houry, Debra
Abstract : Overall, drug overdose deaths have never been higher in the United States with over 63 000 deaths in 2016 alone. That year, two-thirds of drug overdose deaths involved an opioid. The impact of opioids is so pronounced that life expectancy decreased in the United States for the second consecutive year. The U.S. opioid overdose epidemic began in the late 1990s with deaths from prescription opioids increasing in lockstep with more proliferate prescribing practices. As prescription opioid-related deaths began to plateau in 2010, the heroin-related death rate increased almost 5-fold since then. More recently, the death rate from synthetic opioids other than methadone increased 6-fold since 2013 with illicitly manufactured fentanyl driving this increase. Unfortunately, the death rate from prescription opioids increased in 2016 too and has never been higher. The U.S. Centers for Disease Control and Prevention (CDC) works to prevent opioid-related morbidity and mortality including overdose, opioid use disorder, neonatal abstinence syndrome, hepatitis C infection, and other outcomes. CDC aims to improve data quality and track trends, to strengthen state capacity to scale up evidence-based interventions, to improve patient safety by giving clinicians the data, tools and resources they need, and to empower people to make safer choices with opioids. As deaths from illicit opioids increased, the CDC response expanded and involves enhancing collaboration and coordination with police and others in public safety. This presentation will provide an overview of the burden of the opioid epidemic in the United States and the multifaceted and multisector CDC response. It will include information about getting more timely, localized, and actionable surveillance data, funding states to tailor their prevention efforts, implementing the CDC Guideline for Prescribing Opioids for Chronic Pain, launching a successful prescription opioid communication campaign, and working more closely with public safety officials to accelerate community-level responses.